c-Cbl, a Ubiquitin E3 Ligase That Targets Active β-Catenin: A NOVEL LAYER OF Wnt SIGNALING REGULATION - Chitalia, Vipul (J Biol Chem, 2013)
Regulation of transcriptionally active nuclear β-catenin during the Wnt-on phase is crucial to ensure controlled induction of Wnt target genes. Several ubiquitin E3 ligases are known to regulate cytosolic β-catenin during the Wnt-off phase, but little is known about the fate of active nuclear β-catenin in the Wnt-on phase. We now describe ubiquitination of active β-catenin in the Wnt-on phase by a RING finger ubiquitin E3 ligase, Casitas B-lineage lymphoma (c-Cbl) in endothelial cells. c-Cbl binds preferentially to nuclearly active β-catenin in the Wnt-on phase via the armadillo repeat region. Wild-type c-Cbl suppresses and E3 ligase-deficient c-Cbl-70Z increases Wnt signaling. Wnt induces nuclear translocation of c-Cbl where it ubiquitinates nuclear β-catenin. Deletion of the c-Cbl UBA domain abrogates its dimerization, binding to β-catenin, Wnt-induced c-Cbl nuclear translocation, and ubiquitination of nuclear β-catenin. c-Cbl activity inhibits pro-angiogenic Wnt targets IL-8 and VEGF levels and angiogenesis in a β-catenin-dependent manner. This study defines for the first time c-Cbl as a ubiquitin E3 ligase that targets nuclearly active β-catenin in the Wnt-on phase and uncovers a novel layer of regulation of Wnt signaling.